Fibroblast Growth Factor 2 Drives Changes in Gene Expression Following Injury to Murine Cartilage In Vitro and In Vivo. Issue 9 (26th August 2013) - Chong, Ka‐Wing; Chanalaris, Anastasios; Burleigh, Annika; Jin, Huilin; Watt, Fiona E.; Saklatvala, Jeremy; Vincent, Tonia L.
Abstract : Objective: The articular cartilage is known to be highly mechanosensitive, and a number of mechanosensing mechanisms have been proposed as mediators of the cellular responses to altered mechanical load. These pathways are likely to be important in tissue homeostasis as well as in the pathogenesis of osteoarthritis. One important injury‐activated pathway involves the release of pericellular fibroblast growth factor 2 (FGF‐2) from the articular cartilage. Using a novel model of murine cartilage injury and surgically destabilized joints in mice, we examined the extent to which FGF‐2 contributes to the cellular gene response to injury. Methods: Femoral epiphyses from 5‐week‐old wild‐type mice were avulsed and cultured in serum‐free medium. Explant lysates were Western blotted for phospho‐JNK, phospho‐p38, and phospho‐ERK or were fixed for immunohistochemical analysis of the nuclear translocation of p65 (indicative of NF‐κB activation). RNA was extracted from injured explants, rested explants that had been stimulated with recombinant FGF‐2 or FGF‐18, or whole joints from either wild‐type mice or FGF‐2 −/− mice. Reverse transcription–polymerase chain reaction was performed to examine a number of inflammatory response genes that had previously been identified in a microarray analysis. Results: Murine cartilage avulsion injury resulted in rapid activation of the 3 MAP kinase pathways as well as NF‐κB. Almost all genes identified in murine joints following surgical destabilization were also regulated in cartilage explants upon injury. Many of these genes, including those for activin A ( Inhba ), tumor necrosis factor–stimulated gene 6 ( Tnfaip6 ), matrix metalloproteinase 19 ( Mmp19 ), tissue inhibitor of metalloproteinases 1 ( Timp1 ), and podoplanin ( Pdpn ), were significantly FGF‐2 dependent following injury to cartilage in vitro and to joint tissues in vivo. Conclusion: FGF‐2–dependent gene expression occurs in vitro and in vivo in response to cartilage/joint injury in mice.